Video Capsule Endoscopy in the Assessment of Portal Hypertensive Enteropathy. (1st November 2018) - Al-Azzawi, Yasir; Spaho, Lidia; Mahmoud, Mohammed; Kheder, Joan; Foley, Anne; Cave, David
Abstract : Background. The features of the portal hypertension enteropathy (PHE) vary from mild mucosal changes to varices with or without bleeding. The prevalence and the development are not fully understood. Aim. Our aim is to examine the prevalence and the different manifestations of PHE using video capsule endoscopy (VCE). Methods. It is a single center retrospective study of patients with cirrhosis, who had VCE. Based on the published literature, we divided the PHE lesions into vascular lesions and mucosal lesions. Results. Of the 100 patients with cirrhosis that had a VCE study, the mean age was 62.82 years. Male gender was predominant (64%), while Caucasians represented 82% of the cohort. The most common etiology of cirrhosis was chronic alcohol abuse followed by chronic hepatitis C virus and nonalcoholic steatohepatitis. VCE detected small bowel lesions in 71% of the patients while the features of PHE were found in 65% from the total cohort. AVMs and inflammatory changes were the most common findings, followed by bleeding. More than 50% of the lesions were vascular in nature. The risk of finding PHE in decompensated cirrhosis is twice that in compensated cirrhosis. Forty-five patients had negative EGD exam for any active bleeding, esophageal varices, portal hypertensive gastropathy, or gastric varices. Of these, 69% had features of PHE in their VCE. Conclusions. VCE detected small bowel lesions in 71% of our cohort. There is a high prevalence of PHE in decompensated cirrhosis. Vascular lesions are the most common finding in the small bowel of this population.